Probing Solar Modulation of AMS-02 Time-dependent D, 3He, and 4He Fluxes with Modified Force-field Approximation Models - Zhu, Cheng-Rui; Wang, Mei-Juan (The Astrophysical journal, 2025)
The AMS-02 experiment recently published time-dependent fluxes of deuterons (D) from 2011 May to 2021 April, divided into 33 periods of four Bartels rotations each. These temporal structures are associated with solar modulation. In this study, three modified force-field approximations (FFAs) are employed to examine the long-term behavior of cosmic-ray isotopes such as D, 3He, and 4He, as well as the ratios D/3He and 3He/4He. The solar modulation potential is rigidity dependent for these modified FFA models. Due to the unknown local interstellar spectrum (LIS) for these isotopes, we utilize the non-LIS method for solar modulation. By fitting to the AMS-02 time-dependent fluxes, we derive the solar modulation parameters. Our findings prove the assumption in literature that all isotopes can be fitted using the same solar modulation parameters, and it is shown that the modified FFA models provide valid parameterization for solar modulation. Based on these, we forecast the daily fluxes of D, 3He, and 4He from 2011 to 2020.